ANALISIS KESULITAN BELAJAR SISWA KELAS X PADA PEMBELAJARAN ONLINE MATA PELAJARAN GEOGRAFI DI MAN 1 PASAMAN SELAMA PANDEMI COVID 19 - Elya Fitrina; Khairani Khairani (JURUSAN GEOGRAFI FIS UNP, 2021)
ABSTRACT This study aims to analyze the learning difficulties of class X students in online learning in geography subjects at school. This research is a descriptive quantitative research. The population in this study were all students of class X IPS MAN 1 Pasaman, totaling 113 students, while the sample was taken from class X IPS 1 with a total of 38 students. The data collection methods are questionnaire or questionnaire, interview and documentation. The data analysis technique in this research is the initial process of the data processing stage, and quantitative analysis with the final results in the form of percentages and descriptions. The results of this study indicate that the majority of class X students have difficulty learning in online learning geography subjects with a percentage of 68.4% or 26 students of 38 students of class X Ips 1 at MAN 1 Pasaman. The difficulties experienced by students are due to several factors, among others, students do not have special study schedules at home, teachers are not clear in delivering material and so on. This can be overcome by teachers having to provide motivation to students, teachers must have varied teaching strategies to generate student Keywords: Learning Difficulties, Online Learning and the Covid Pandemic 19